Teologi Multikultural: Kearifan Lokal Sebagai Bentuk Berteologi dan Berbudaya - Frets Keriapy (MAGENANG : Jurnal Teologi dan Pendidikan Kristen, 2020)
Christianity is a religion that can be said to be quite large and growing rapidly in the world. Since the first time people who believed in Jesus Christ as Lord and Savior were called Christian in Antioch, the development in terms of quantity continued to increase and eventually spread to Indonesia through missionaries from the Western world. Along with the development on the field of technology and information era, this makes people consider culture as an ancient thing that needs to be abandoned. Not only technology, with the development of Western theology, makes culture lost without trace. Western theology views culture as an idol and therefore according to Christian teachings that Christians should not be involved in it. This paper will provide a new horizon where theology and culture should not be the two things that should not be hostiled to each other but both must be united so that the cultural community can interpret its faith more concretely. The method used in this research is a qualitative description method using literature study and also theories that are used as a tool to look back at theology in a plural society system. The attitude of Christians towards culture is strongly influenced by the construction of theology that is built. Therefore, it is important to look back and review the theology that develops in culture. In addition, studying the Bible's view of culture and how theology should behave is of the utmost importance. At the end of this paper, the author will contribute giving the thoughts on how theology is manifested in a pluralistic culture.